Assessing land use/land cover change detection of north-eastern watersheds of Kashmir valley using GIS and remote sensing techniques - Sarvat Gull; Shagoofta Rasool Shah; Ayaz Mohmood Dar (Water Practice and Technology, 2022)
Land use changes in the Kashmir Himalayas must be mapped and monitored for long-term development and efficient planning. This work uses geospatial technologies such as remote sensing and geographic information system to track changes in land cover trends in four main watersheds in the Kashmir Valley's north-eastern Himalayas from 2003 to 2013. Land cover maps were created using images from the Landsat-5 Thematic Mapper. The watershed's land use/land cover (LULC) maps were created using supervised classification utilizing the maximum likelihood classifier (MLC). Over the previous decade, the LULC in the study watersheds has undergone a series of intricate changes as a result of deforestation, climate change, and agroforestry growth. A total of 11 major LULC classifications were discovered, indicating that forests are the most common land use in all four watersheds. Forest cover, river beds, water bodies, non-perennial snow, and glaciers have all decreased significantly, whereas scrubland, horticulture, rock mass, built-up areas, barren land, and agriculture have all increased significantly, except for Sindh watershed, where the scrubland class has decreased by 5.97% from 2003 to 2013. The study's methodology and conclusions point to crucial policy implications for long-term LULC management in the Kashmir Himalayas' Madhumati, Arin, Sindh, and Lidder watersheds. HIGHLIGHTS The current study makes use of the remote sensing and GIS approach, which is currently one of the most popular technologies for spatio-temporal analysis.; As a result of deforestation, climate change, and agroforestry expansion, the LULC in the study watersheds has undergone a series of complex changes during the past decade.; Forest cover has decreased drastically while agroforestry has shown an increasing trend.;